FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KEJADIAN PREEKLAMPSIA BERAT PADA IBU HAMIL DI RSD RADEN MATTAHER JAMBI TAHUN 2007 - Sri Yun Utama (Jurnal Ilmiah Universitas Batanghari Jambi, 2008)
One of the main causes of womens death is preeclampsia. This desease is indicated by chypertention, oedema and proteinuria. Unfortunately,women do not have enough knowledge about the symptoms of this descase. Consequently, it is always too late to take necessary measures resulting other complication. This research aims to identify the risks of serious preeclampsia on pregnant women in Raden mMataher Hospital of Jambi. This research is an analytical one with case control design. The population was pregnant women with serious preeclampsia hospitalized in the miduwi fery ward of Raden Mattaher Hospital (case) and women with normal pergnancy  visiting midwifery policlime of Raden Mattaher Hospital (control). The sample was selected randomly. This research was conducted from february untill march in 2008 using secondary data which was analyzed with univariate and bivariate techniqnes the result of the analysis shows that 74,1% of the sample have no risks of age (20-35 years), 62,4 % happens on multigravida, pregnancy age >28 weeks, 86,9 % have no history of the desease. It also shows that womens age their prenancy age and history of the desease significantly correlate with serious preeclampsia. From the finding, it can be concluded that there are many factors that effect serious preeclampsia. There fore, doctors and paramedics of Raden Mattaher Hospital should improve their service in the hospital espicially in the midwifery word. It is also suggested that they do 7 T for antenatal care patient with and without risky factors because regular antenatal examinations is significant for preeeclampsia prevention.